SYNTHESIS, SPECTROSCOPIC PROPERTIES, AND CRYSTAL STRUCTURE OF 1-NAPHTHYL(1- METHYLETHYLIDENE)IMINIUM CHLORIDE - Al-Masri, Harbi Tomah; Moussa, Ziad (European Scientific Journal, ESJ, 2014)
Condensation of 1-naphthylamine with acetone in the presence of Et3N·HCl as a catalyst gave the corresponding 1-naphthyl (1- methylethylidene) iminium chloride (1). The salt was identified and characterized by multinuclear NMR (1H and 13C NMR) and IR spectroscopy. In solution, the two methylenic hydrogens of the N-isopropyl moiety are anisochronous. This result was confirmed by the X-ray investigation of 1 in the solid state. 1 crystallized in the orthorhombic space group Pbca, a = 10.8668(8)Å, b = 11.1758(9) Å, c = 18.8726(18)Å, α = γ = β = 90 °, Z = 8. The structure was solved by direct methods, and retined by full-matrix least squares techniques to an R factor of 0.0308 for 1874 observed reflections. In the crystal the 1-naphthyl (1-methylethylidene) iminium cation and chloride anion are linked by N–H···Cl hydrogen bond.